Parametric study on thermal performance augmentation of TiO2/water nanofluids flowing a tube contained with dual counter twisted-tapes - Chinaruk Thianpong; K. Wongcharee; K. Kunnarak; S. Chokphoemphun; Sunil Chamoli; Smith Eiamsa–ard (Case Studies in Thermal Engineering, 2024)
The study of compound heat transfer enhancement technique using dual counter twisted tapes (DCTs) together with TiO 2 /water nanofluids was carried out. The dual twisted tapes in form of counter-swirl tape arrangement were utilized at three twist ratios ( y/w = 1.5, 2.0 and 2.5). TiO 2 /water nanofluids having three different volume concentrations ( φ = 0.05, 0.10 and 0.15 %) were employed as the testing fluids. The results indicated that heat transfer rate, friction factor and thermal enhancement index rose with decreasing tape twisted ratio and elevating nanofluid concentration. The TiO 2 /water nanofluids applied in the present work offered higher Nu than pure water (the base fluid) by 7.3–10.0 %. The application of DCT with the smallest y/w of 1.5 and TiO 2 /water nanofluids with the largest φ of 0.15 vol% led to the highest thermal enhancement index (TEI) of 1.53, under the same pumping power criteria. Additionally, the k-nearest neighbor (k-NN) and artificial neural network (ANN) were developed to predict the thermal enhancement index (TEI). It was found that the k-NN and ANN models provided maximum R 2 values of 0.919 and 0.992 f, respectively.
Keywords: Nanofluid Flow and Heat Transfer; Solar Thermal and Photovoltaic Systems; Heat Transfer and Boiling Studies